Analisis Kesulitan Siswa Kelas 1 SDN 1 Pedawang dalam Memahami Soal Cerita Matematika Akibat Rendahnya Kemampuan Literasi dan Numerasi - Firdausi Zula, Yukhanit; Aryani, Dias Syifa; Riswari, Lovika Ardana (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Mathematics learning in Elementary School is very important to form logical, systematic, and critical thinking skills. Mathematics learning is closely related to numeracy literacy. At the elementary school level, especially grade 1, literacy and numeracy problems are increasingly visible when students are faced with mathematical story problems. In grade 1 of SDN 1 Pedawang, the results of daily tests and end-of-semester tests show that students' ability to solve story problems is still low. This study aims to analyze the difficulties of grade 1 students at SDN 1 Pedawang in understanding mathematical story problems due to low literacy and numeracy skills. This study uses a qualitative descriptive research type. The population of grade 1 students at SDN 1 Pedawang is 14 students, consisting of 9 female students and 5 male students. The subjects used were 2 students to be analyzed using purposive sampling techniques because they showed striking difficulties in understanding story problems based on observation results and low test scores. Data collection techniques through observation, interviews, and documentation. Data analysis techniques using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study showed that students had difficulty in understanding mathematical story problems on five indicators according to Newman's theory, namely reading, understanding, transformation, process skills, and writing answers. The conclusion of this study shows that low literacy and numeracy of students are the main factors in the difficulty of understanding mathematical story problems.